Carruthers Peter, The Architecture of the Mind: Massive Modularity and the Flexibility of Thought - Liza Skidelsky (Crítica)
Peter Carruthers, The Architecture of the Mind: Massive Mod- ularity and the Flexibility of Thought, Oxford University Press, Oxford, 2006, 462 pp.